Gastroesophageal reflux in children with functional constipation - Maşallah Baran; Funda ÖZGENÇ; Çiğdem ARIKAN; Murat Çakır; Çiğdem ÖMÜR ECEVİT and Sema Aydoğdu and Raşit Vural YAĞCI (Turkish Journal of Gastroenterology, 2019)
-